Christendom Witnesses to the Martyrs: Modulations of the Acta Martyrum in Prudentius' Peristephanon, vi - Bilby, Mark Glen (The journal of ecclesiastical history, 2012)
In hymn vi of his Peristephanon, Prudentius dramatically reworks the plot of the Passio Fructuosi. The poet turns the perpetrators from well-known and dutiful representatives of a transient empire into despicable caricatures of evil and vice, transforms the martyred bishop from a caring pastor into a heroic leader of heroes, re-narrates the roles of Christian family members as anonymous martyr-cult devotees, and shifts the focus from the martyred bishop as a local, beloved model of imitation and encouragement during a time of persecution to the three martyrs together as co-equal objects of worship and patrons and saviours of their region and devotees.